Effect of hydroxyapatite nanoparticles addition on structure properties of poly(l‐lactide‐co‐glycolide) After gamma sterilization. Issue 4 (15th April 2016) - Urbanek, Olga; Pierini, Filippo; Choińska, Emilia; Sajkiewicz, Paweł; Bil, Monika; Święszkowski, Wojciech
Abstract : Physical and chemical factors resulting from the sterilization methods may affect the structure and properties of the materials which undergo this procedure. Poly(l ‐lactide‐ co ‐glicolide) (PLGA) is commonly used for medical applications, but, due to its inadequate mechanical properties, it is not recommended for load‐bearing applications. One of the methods for improving PLGA mechanical properties is addition of hydroxyapatite nanoparticles (nHAp). The aim of this study was to evaluate the effect of nanoparticles addition on PLGA structure and properties after gamma radiation. According to our results, reduction of the molecular mass caused by gamma radiation was lower for PLGA with nHAp addition. Differential scanning calorimetry (DSC) analysis indicates an increase of crystallinity caused both by nHAp and gamma radiation. The first phenomenon can be explained by heteronucleation, while the second one is most probably related to higher molecular mobility of degrading polymer. Moreover, addition of nanoparticles increases thermal stability and affects the Young's modulus changes after gamma radiation. POLYM. COMPOS., 39:1023–1031, 2018. © 2016 Society of Plastics Engineers